2016
DOI: 10.1590/0103-8478cr20150507
|View full text |Cite
|
Sign up to set email alerts
|

Indirect diagnostic tests for the detection of subclinical mastitis in dairy goats experimentally infected with Staphylococcus aureus

Abstract: The aim of the present study was to assess two diagnostic techniques (California mastitis test (CMT) and the somatic cell count (SCC)) that can diagnose mastitis in dairy goats

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…SCC levels in milk were high during the first few days after infection and then gradual decreased after intramammary treatment. As a result, SCC appear to be useful in predicting the infectious state of the udder (16).…”
Section: Discussionmentioning
confidence: 99%
“…SCC levels in milk were high during the first few days after infection and then gradual decreased after intramammary treatment. As a result, SCC appear to be useful in predicting the infectious state of the udder (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the intra-mammary infections in sheep may also affect due the teats placement and udder conformation where the small udder, horizontally teats and inappropriate udder confirmation (deep and pendulous udder) may increase exposure to injury and contamination and then related to greater risk of mastitis disease [23]. Previously, [24] co-worker also confirmed that the pendulous udder was significantly associated with mastitis, whereas subclinical mastitis is invisible and relies on somatic cell count (SCC) or California Mastitis Test (CMT) as an indicator [25][26][27]. Thus, this situation has raised the concern among farmers or dairy producers since undiagnosed subclinical mastitis can probably be an possible source of infection for other lactating animals.…”
Section: Introductionmentioning
confidence: 99%